The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/trf.12424
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative management of severe acute anemia in a Jehovah's Witness

Abstract: This case is an example of the resilience of the human body in an extreme circumstance. It might be the most severe case of anemia that a person has survived without any sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Before this study, Viele and Weiskopf had performed a systematic literature search and identified 54 published reports with discernible data featuring 134 Jehovah's Witness patients with Hb levels of not more than 8 g/dL who were managed without transfusion. Other available literature in the field is predominantly individual case reports or limited case series, cohorts that were subsequently included in the study by Carson and colleagues, or cohorts of patients with higher Hb levels …”
Section: Discussionmentioning
confidence: 99%
“…Before this study, Viele and Weiskopf had performed a systematic literature search and identified 54 published reports with discernible data featuring 134 Jehovah's Witness patients with Hb levels of not more than 8 g/dL who were managed without transfusion. Other available literature in the field is predominantly individual case reports or limited case series, cohorts that were subsequently included in the study by Carson and colleagues, or cohorts of patients with higher Hb levels …”
Section: Discussionmentioning
confidence: 99%
“…While the data is conflicting, case reports document survival in JW patients with extremely low Hb levels (down to 10 g/L) with aggressive use of ESAs and/or other supportive measures 15,16 . The use of ESAs are at the discretion of the local unit, requiring local hospital drug committee authorisation and informed consent explaining the risks of hypertension and thrombosis.…”
Section: Erythropoiesis-stimulating Agents (Esas): Erythropoietin Damentioning
confidence: 99%
“…Survival of transient acute anemia (hemoglobin 7 g/l) was reported [63]. Even without allogeneic blood transfusion, a nadir hemoglobin of 14 g/l was survived by a patient refusing blood products [64].…”
Section: Acute Anemia Hemodilution and Anemia Tolerance (The Individmentioning
confidence: 99%